Dedifferentiation patterns in DTC: is PDTC an intermediate state between DTC and ATC? - Wen, Duo (Int J Clin Exp Pathol, 2019)
Purpose: The majority of poorly differentiated thyroid cancer (PDTC) and anaplastic thyroid cancer (ATC) are thought to dedifferentiated from differentiated thyroid cancer (DTC). PDTC is regarded as an intermediate form, through which DTC dedifferentiates into ATC. Although accumulation of gene mutations has been observed in PDTC and ATC, evidence of a direct link between DTC, PDTC, and ATC is still lacking. This work aims to illustrate if PDTC is the intermediate state between DTC and ATC. Patients and methods: Whole-exome sequencing was performed in a single patient presenting with primary papillary thyroid cancer (PTC) with simultaneous PTC, PDTC, and ATC in metastatic lymph nodes. Results: 167 nonsynonymous mutations were identified, and 24 of them were exclusive to metastatic loci. Comparison of mutational spectra revealed following results: 1) PDTC and ATC were associated with PTC-LN2 but not PTC-LN1; 2) the majority (5/6) of non-ubiquitous mutations in ATC were also present in PDTC; and 3) despite one mutation observed simultaneously in PTC-LN2, PDTC and ATC, no other associations were found between the ATC and PTC samples (primary or metastatic). Additionally, we identified five mutations (four mutations present in both PDTC and ATC, and one exclusive to ATC), including TP53 p.N107_S108delinsX, possibly related with DTC dedifferentiation. Conclusions: We observed an apparent potential, stepwise dedifferentiation process linking DTC, PDTC, and ATC, with PDTC serving as an intermediate state between DTC and ATC in one certain patient. One key mutation, combined with several low-frequency mutations, appears to underlie this dedifferentiation pathway.